LINGUISTIC ADAPTATION IN SEVERAL LANGUAGES IN ARFAK MOUNTAINS, MANOKWARI, WEST PAPUA - Mukhamdanah . (Metalingua: Jurnal Penelitian Bahasa, 2015)
THE influence from one language to another can be seen through the borrowingsfrom another language. It is the feature of language universality. The emergenceof new vocabulary reflects the language openness to influence from anotherlanguage and the language of the receiver will develop. Such influence occurredin four languages of Arfak mountains in Manokwari. Linguistic adaptationoccurred due to language contact amongst the speakers within the area. Thelanguage of Biak, Mansinam, Hatam, and Mansim Borai were the subject tostudy. Lexicostatistic method upon two hundred vocabularies of each languagewas used to determine the relationship among those languages. Sound changesupon the sets of cognate words or sets of words assumed to derive from the samesource show the occurrence of linguistic adaptation as the result of languagecontact. Linguistic adaptation found was prothesis, epenthesis, paragoge,aphaeresis, syncope, apocope, and sound variations in the four languages. Themost linguistic adaptation occurred was sound variations, prothesis, aphaeresis,and apocope. The highest percentage of linguistic adaptation was found in Biaklanguage and Mansinam language and between Mansim Borai language andHatam language.